Levantamento epidemiológico da queilite actínica em trabalhadores rurais da microrregião sergipana do sertão do São Francisco - Martins Filho, Paulo Ricardo Saquete (2010)
Solar radiation as a major risk factor for development of actinic cheilitis and lip cancer has been discussed in recent decades, particularly due to destruction of the ozone layer and increased incidence of ultraviolet radiation on different parts of the world. In Brazil, these lesions are of fundamental importance, because it is a country of low latitude and include in its economy outdoor activities, such as agriculture, livestock and fisheries. Carry out an epidemiological survey of actinic cheilitis among farm workers in São Francisco sertão microregion, Sergipe State. Cross-sectional study conducted in the semi-arid region of Sergipe State whose variables investigated included gender, skin color, age, cumulative and daily exposure time to solar radiation, tobacco consumption, sunscreen use and presence of actinic cheilitis. For cases diagnosed as actinic cheilitis, data about location, clinical features and symptoms were recorded. The degree of epithelial atypia was obtained by biopsy and histopathological analysis. Disease measure risk in relation to the variables, we used the prevalence ration and confidence interval of 95%. The statistical treatment of data was done through tests of association (Pearson s chi-square and linear-by-linear association) and comparison between two means (Mann-Whitney), adopting significance level of 5%. We examined 240 farm workers and found a prevalence of actinic cheilitis of 16.7%. There was a significant association between presence of disease in males, white skin type, age over 50 years, duration of daily exposure to solar radiation of more than 8 hours and smoking habits. The linear trend test showed a positive relationship between cumulative exposure time and the development of actinic cheilitis. In relation of sunscreen usage, there was preference for straw hat, with reports of occasional application of lipstick sunscreen. All cases of actinic cheilitis were observed in the lower lip, with atrophy and erythema as the most striking of the presence of the disease. Complaint of pain was reported by only 27.5% of affected farm workers. Approximately 35% of cases showed histopathological changes consistent with the presence of severe epithelial dysplasia. The farm workers of São Francisco sertão microregion are a population at high risk for lip cancer, since it is high prevalence of actinic cheilitis in the region and is common the sun exposure and tobacco use among these people. It is necessary to carry out education campaigns about the risks of chronic exposure to solar radiation among farm workers in the semi-arid zone and sunscreen use reinforcement.